Evaluation of ultrasound-measured gastric volume and content in type 2 diabetes mellitus patients undergoing elective surgery: a prospective observational study - Demirel, Asiye; Dayıoğlu, Mürüvvet; Balkaya, Ayşe Neslihan; Onur, Anıl; Gözen, Füsun (The European Research Journal, 2023)
Objectives: Delayed gastric emptying create a risk of pulmonary aspiration during anesthesia. We aim to assess the antral cross-sectional area (CSA) and gastric volume using ultrasound techniques and to investigate the relationship between these variables and both the duration and regulation of type 2 diabetes mellitus (DM). Methods: Gastric volume was estimated by measuring the antral CSA in the supine and right lateral decubitus (RLD) positions in 80 patients. The antral content was qualitatively classified according to Perlas et al. (grades 0, 1, and 2), and gastric volume was computed using a previously described formula. The presence of solid content or > 1.5 mL/kg fluid in the stomach was classified as indicative of a full stomach. Results: The mean duration of diabetes among the subjects was 9.4 ± 3.7 years. The mean fasting duration was 10.2 ± 2.1 hours for solids and 2.5 ± 0.7 for liquids. Twelve of the 80 patients exhibited grade 2 stomach. Age (p = 0.005), Body mass index (p = 0.001), solid fasting duration (p = 0.027), and supine and RLD CSA (p < 0.001 for both) were significantly associated with full stomach. A history of ≥8 years of diabetes (p < 0.001) and peripheral neuropathy (p = 0.005) was identified as a risk factor for a full stomach. Conclusions: Despite adherence to standard fasting protocols, 15% of the type 2 DM patients were identified with a ’full stomach’ condition. Preoperative ultrasound assessment of gastric contents in patients with type 2 DM, especially with long-standing diabetes (≥ 8 years) and with peripheral neuropathy is recommended. The findings of this study necessitate additional investigation to support the conceptualization of specific guidelines for diabetes to mitigate the risk of pulmonary aspiration.